Characterization of novel mutants of hexaploid wheat (Triticum aestivum L.) with various depths of purple grain color and antioxidant capacity. (3rd July 2018) - Hong, Min Jeong; Kim, Dae Yeon; Nam, Bo Mi; Ahn, Joon‐Woo; Kwon, Soon‐Jae; Seo, Yong Weon; Kim, Jin‐Baek
Abstract: BACKGROUND: Wheat grain is recognized as a rich source of nutrients, including proteins, vitamins, minerals, fibers and antioxidants. In recent years, the focus of wheat breeding has been to increase the content of bioactive compounds to improve human health and prevent diseases. RESULTS: Five novel wheat mutant lines with variable seed color were developed using gamma irradiation of hexaploid wheat inbred line K4191 (purple seed color). The total anthocyanin contents of three mutant lines (L47, L167 and L925) were significantly higher than those of wild‐type lines, including K4191 and 'Keumkang' (white seed color). L925 showed the highest total anthocyanin content, and cyanidin‐3‐glucoside was presented as the most predominant anthocyanin. Compared with 'Keumkang', the expression of anthocyanin biosynthesis genes was significantly up‐regulated in purple seed mutant lines. The highest antioxidant activity was observed in L925 extracts. The expression of a few antioxidant‐related genes and total anthocyanin content were positively correlated with antioxidant capacity. These data suggest that anthocyanins and phenolic compounds in wheat grains contribute to the antioxidant potential. CONCLUSION: Purple grain color is associated with higher anthocyanin accumulation and antioxidant capacity in wheat. Wheat mutants developed in this study may serve as a valuable source of antioxidants. © 2018 Society of Chemical Industry